The Effect of Fanatism, Price and Location on Buying Interest and Ticket Purchase Decisions for South Korean Band Concerts at The Jawa Pos Arena Building - Adinda Restiningtyas; Alfizi Alfizi; Puspita Lianti Putri (Jurnal Manajemen Bisnis, 2025)
The study used a quantitative approach with an online survey method distributed to 230 participants who had purchased tickets. Data analysis was carried out using the SEM-PLS method using SmartPLS software. The results of this study indicate that fanaticism has a significant positive impact on purchasing interest and purchase decisions. Price has a positive impact on purchasing interest but not on purchasing decisions, while location has no positive impact on purchasing interest and purchase decisions, and purchasing interest has a positive impact on purchasing decisions. The following findings explain that in the context of K-pop concerts, emotional factors such as fanaticism are more dominant than rational factors such as price and location. The phenomenon of K-pop concerts in Surabaya is the first. Day6 is a South Korean artist to perform a concert in Surabaya, so researchers are interested in examining the influence of fanaticism, price, and location factors on purchasing interest and ticket purchase decisions for a South Korean band concert at the Jawa Pos Arena in Surabaya. Theoretically, this can contribute to the development of science in the marketing and consumer behavior sectors. Meanwhile, practically, it can contribute to promoters or concert organizers by providing suggestions to consider more emotional aspects in marketing strategies, as well as choosing locations that are comfortable, safe, and easily accessible.